PPARγ as a Potential Target to Treat Airway Mucus Hypersecretion in Chronic Airway Inflammatory Diseases - Yongchun Shen; Lei Chen; Tao Wang; Fuqiang Wen (PPAR Research)
Airway mucus hypersecretion (AMH) is a key pathophysiological feature of chronic airway inflammatory diseases such as bronchial asthma, cystic fibrosis, and chronic obstructive pulmonary disease. AMH contributes to the pathogenesis of chronic airway inflammatory diseases, and it is associated with reduced lung function and high rates of hospitalization and mortality. It has been suggested that AMH should be a target in the treatment of chronic airway inflammatory diseases. Recent evidence suggests that a key regulator of airway inflammation, hyperresponsiveness, and remodeling is peroxisome proliferator-activated receptor gamma (PPARγ), a ligand-activated transcription factor that regulates adipocyte differentiation and lipid metabolism. PPARγ is expressed in structural, immune, and inflammatory cells in the lung. PPARγ is involved in mucin production, and PPARγ agonists can inhibit mucin synthesis both in vitro and in vivo. These findings suggest that PPARγ is a novel target in the treatment of AMH and that further work on this transcription factor may lead to new therapies for chronic airway inflammatory diseases.